Mesoscopic numerical analysis of dynamic tensile fracture of recycled concrete. Issue 6 (10th February 2020) - Ying, Liping; Peng, Yijiang; Kamel, Mahmoud M.A.
Abstract : Purpose: Based on the random aggregate model of recycled aggregate concrete (RAC), this paper aims to focus on the effect of loading rate on the failure pattern and the macroscopic mechanical properties. Design/methodology/approach: RAC is regarded as a five-phase inhomogeneous composite material at the mesoscopic level. The number and position of the aggregates are modeled by the Walraven formula and Monte–Carlo stochastic method, respectively. The RAC specimen is divided by the finite-element mesh to establish the dynamic base force element model. In this model, the element mechanical parameters of each material phase satisfy Weibull distribution. To simulate and analyze the dynamic mechanical behavior of RAC under axial tension, flexural tension and shear tension, the dynamic tensile modes of the double-notched specimens, the simply supported beam and the L specimens are modeled, respectively. In addition, the different concrete samples are numerically investigated under different loading rates. Findings: The failure strength and failure pattern of RAC have strong rate-dependent characteristics because of the inhomogeneity and the inertial effect of the material. Originality/value: The dynamic base force element method has been successfully applied to the study of recycled concrete.